Psychosocial Illness in Children with Diabetes mellitus (Cuestiones de Fisioterapia, 2025)
Type 1 Diabetes Mellitus (T1DM) and psychosocial illness influence each other in multiple ways. The extent of psychosocial disorders in children with T1DM remains largely unstudied in Egypt.